1991
DOI: 10.1029/91jb00176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure, temperature, and composition on lattice parameters and density of (Fe,Mg)SiO3‐perovskites to 30 GPa

Abstract: High‐pressure, high‐temperature properties of MgSiO3, (Fe0.1Mg0.9)SiO3, and (Fe0.2Mg0.8)SiO3 perovskites have been investigated using a newly developed X ray diffraction technique involving monochromatic synchrotron radiation. The first direct measurements of unit cell distortions and equation‐of‐state parameters of the orthorhombic perovskite as functions of composition and simultaneous high pressure and high temperature were obtained. The experiments were conducted under hydrostatic pressure up to 30 GPa, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
131
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(151 citation statements)
references
References 33 publications
20
131
0
Order By: Relevance
“…These values are consistent with the values obtained by ISAAK et al (1992) and ANDERSON and ISAAK (1993) for MgO. They are not compatible with the much higher value of ST obtained for perovskite up to 30 GPa by MAO et al (1991). It is suggested that the value of 6s by AGNON and BUKOwINSKI (1990) is slightly too low.…”
Section: Temperature Dependence Of Incompressibility: the Anderson-grsupporting
confidence: 78%
See 1 more Smart Citation
“…These values are consistent with the values obtained by ISAAK et al (1992) and ANDERSON and ISAAK (1993) for MgO. They are not compatible with the much higher value of ST obtained for perovskite up to 30 GPa by MAO et al (1991). It is suggested that the value of 6s by AGNON and BUKOwINSKI (1990) is slightly too low.…”
Section: Temperature Dependence Of Incompressibility: the Anderson-grsupporting
confidence: 78%
“…But we may suppose that the temperature variations extend further into the lower mantle and that evidence of them may be sought in seismic tomography. Central to this discussion are the temperature dependences of incompressibility, Ks, and rigidity, µ, under lower mantle conditions, which are the subject of several recent discussions (AGNON and BUKOWINSKI, 1990;MAO et al, 1991;ISAAK et al, 1992;ANDERSON and ISAAK, 1993). They are represented by dimensionless parameters 1 (OKs (1) b s a vKs 8T )P, 1 aµ e = avq 8T P…”
Section: Introductionmentioning
confidence: 99%
“…Taking ͟ from Burns (4) and the thermoelastic parameters of perovskite from Mao et al (22), we found that the partial transition pressure of 80 GPa at room temperature would increase by about 30 GPa at 2,000 K (10 GPa increase due to the thermal expansion effect, and 20 GPa increase due to the entropy effect). The estimated thermal expansion effects rely on the assumption ⌬ ϳ R…”
Section: Figmentioning
confidence: 99%
“…An analysis of various reports shows that the range of reported values seem to have a bimodal nature, clustering around low values of about 1.7 x 10-5 K-1 [Wang et al, 1994;Chopelas, 1996;Stacey, 1996) and high values about 4.0 x 10-5 K-1 Mao et al, 1991;Patel et al, 1996).…”
Section: Adiabatic Model For Chemically Homogeneous Lower Mantlementioning
confidence: 99%
“…First, all parameters involved, except p and G, are probably not very sensitive to iron content [Mao et al, 1991;Wang et al, 1994]. So in most cases we used the properties of the Mg end members for both (Mg,Fe)O and (Mg,Fe)Si0 3 (Table 1).…”
Section: Vs=~mentioning
confidence: 99%